Analysis ff Factors That Influence Consumer Decisions to Change Sim Card (GSM Prepaid Card) Study on ULM and Uniska Students in Banjarmasin - Apriya Santi; Rina Rina (PT. Hanken SUkses Jaya, 2022)
The purpose of this study was to examine and analyze the factors that influence the decision to switch brands of prepaid GSM SIM cards. These factors are consumer dissatisfaction, the need for variety, product, product price, product advertising, competitor's brand, sales promotion of competitor's brand product, and product distribution. The data needed, obtained through interviews using a questionnaire. By using purposive sampling method. Hypothesis testing using the Structural Equation Model (SEM) technique with a two-step approach (Two Step Approach to SEM) through the Lisrel 8.54 program. Where the research is here to analyze a product that affects the advertising of competitors' brand products, advertising of competitors' brand products affects the decision to switch brands, the product affects the sales promotion of competitors' brand products, sales promotions of competitors' brand products affect the decision to switch brands, prices affect the sales promotion of products competitor brands, sales promotions of competitors' brand products affect the need for variation, products affect distribution, distribution affects the need for variety, products affect consumer dissatisfaction, consumer dissatisfaction affects the decision to switch brands, consumer dissatisfaction affects the need for variety,and the need to seek variety is also able to develop a new pathway between product prices and consumer dissatisfaction significantly and supports the existing theory.